Europe's revolving doors: Import competition and endogenous firm entry institutions - Povilas Lastauskas (Kiel Institute for the World Economy (IfW), 2013)
The close relationship between politics and enterprises made the revolving door wide open and reinforced business influence on political decisions. The paper analyses relationship between firm entry institutions and import competition inside the EU. Though there is a clear tendency for entry and startup costs to decrease over time and particularly in space, I challenge the view that greater openness to trade automatically leads to improved firm entry institutions. My model enables calculating business entry impediments whereas lobbying game produces structural estimates of the counterfactual levels of trade, prices and earnings had no business obstacles existed. Conditions for active entry barriers are laid down in terms of extensive margin and asymmetries in technology and trade costs. Importantly, the model demonstrates that startling differences in firm regulation can be explained resorting to relative gains and losses accruing in a fully trading network as is the EU. More generally, understanding factors which affect imports is crucial for any model seeking to uncover ex ante welfare effects of trade.
Keywords: C31; E02; F12; F14; F15; F55; 330; trade; entry institutions; firm heterogeneity; foreign competition